Dynamic Control of a DFIG Wind Power Generation System to Mitigate Unbalanced Grid Voltage - Ali M. Eltamaly (IEEE Access, 2020)
This paper presents an improved control strategy for a doubly-fed induction generator (DFIG) during unbalanced grid voltage conditions. The proposed strategy was applied in both synchronization and grid-connected conditions. The synchronization process is carried by controlling the extracted positive and negative sequence components of the stator q-axis voltage to follow the grid q-axis voltage. This strategy can be accomplished by controlling the positive and negative sequence components of the rotor d-axis current. By perturbing the rotor d-axis current, the stator EMF builds up and follows the grid voltage accurately. The stator frequency and the phase difference between the stator and grid voltage are compensated by adjusting the stator d-axis positive and negative voltage components to zero. After synchronization, the proposed control strategy focuses on regulating the average stator active and reactive power control by controlling the positive components of q and d-axis currents, respectively. The second target is to minimize the generator torque ripple by controlling the rotor negative sequence components. At the same time, the grid side converter is controlled to minimize the grid power pulsations to reduce the impact of the unbalanced grid voltage. This study focuses on enhancing the dynamics of DFIG during the unbalanced grid voltage by using Multivariable State Feedback (MSF) current controllers. Experiments are carried out to validate the performance improvement by using the proposed method. The simulation and experimental results showed superior performance of the proposed control strategy.